Quadrifurcation of Coeliac Trunk- A Case Report - Rohan A Gawali; Ujwal Gajbe; Trupti Balwir; Sumedha Anjankar; Vaibhav Anjankar (Indian Journal of Forensic Medicine & Toxicology, 2021)
During routine dissection of a cadaver in the department of anatomy at Seth GS Medical College and KEMHospital, we discovered a very rare type of branching pattern of the Coeliac Trunk (CT). The CT measured3cm in length and was quadrifurcating into replaced right hepatic artery, common hepatic artery, left gastricartery and splenic artery. The replaced right hepatic artery had unusual course where it ran behind theportal vein and bile duct to reach the right lobe of liver. Common hepatic artery after giving gastroduodenaland right gastric artery continued as middle hepatic artery while left hepatic artery originated from leftgastric artery. A complete knowledge of these variations are helpful for hepatobiliary surgeons and also forradiologists.